Contribution Of Fishing Communities and The Level Of Acceptance In The Mangrove Forest Ecosystem of Jenggalu Kito Village - Herlena, Feby; Sumartono, Eko; Yumiati, Yossi (SINTA Journal (Science, Technology, and Agricultural), 2024)
Â The ecosystem of the mangrove forest area in Gading Cempaka District, Bengkulu City is an ecotourism area dominated by mangrove trees which have many benefits, one of which is as a barrier to abrasion and there is a lot of marine biota available. The aim of this research is to formulate an analysis of revenue and contribution.The data sources for this research were obtained from questionnaires, interviews, observation and documentation using acceptance, contribution and livelihood analysis. The results of the research can show that the acceptance and contribution of the Jenggalu Village communityÂ is in the medium category (60.32)%. From these calculations it can be concluded that revenue and contribution are not in the low or high category but in the medium category because the variables are at (33.34-66.66)%